Foreign Language Teaching Methodology Requirements - Hikmatovna, Jabborova Nafisa; Sharapovna, Sharapova Gulshan; Baqoyevna, Ikromova Maqsuda; Erkinovna, Tursunova Mavluda; O’ktamovich, Rajabov Axtam (International Journal of Psychosocial Rehabilitation, 2020)
Language learning is one of the most important areas of human society. The language of communication can be practiced in the natural environment (in the family, in the community), or in an organized manner (in the classroom). Knowledge of language phenomena is theoretical. In today's international relations, multilingualism, especially polyglossia, is of the utmost importance. Students studying in Uzbekistan usually learn three languages. “Most of our cognitive youth have three languages.” 1. These languages                                      have special names in educational theory: mother tongue, second language, and foreign language. Native language is the first language that has a special role in thinking. According to psychologists, "thinking is verbal", that is, thought is closely related to the word. Concepts used in the context of native words are used in the sounds and writing of other languages                                      when learning a second or a foreign language. The native language, the second language, and a foreign language (eg non - хлеб - bread) are three in number, but the notion that they form is the only one: “dough, flour, baking, closing food is what is necessary for survival”. In short, linguists are, in a sense, a universal, international phenomenon, and the phonetic and graphic representation of the word is national.